The Influence Of Online Games On Students Language Behavior: Identifying the Use of Taboo Words Among Students at English Education Study of UKI Toraja - Shilfani, Shilfani; Sirande, Normalia; Tangdialla, Novric Caesar (Universitas Cokroaminoto Palopo, 2023)
Abstract contains a brief description of the problem and research objectives, The purpose of this study is to find types the taboo words are very often used by students who play online games in the 7th semester English education study program of UKI Toraja. Data were collected using a questionnaire distributed to 6 7th semester English education students who play online games. This research used quantitative methods then the results of the research were analyzed descriptively. The results found several taboo words that were very often used by students who play games. 2 is the category of curse taboo words, 1 blasphemy, 2 obscenity and 1 name calling and insulting. The cursing category taboo words that were very often used are “fuck and damn” then the blasphemy category taboo word that were very often used is “oh my god” then the obscenity category taboo word that were very often used is “shit and motherfucker” and the category taboo word calling names and insults that are often used is “nigger”. The conclusion of this study found that there are 6 taboo words that are often used by UKI Toraja English education students, namely “fuck”, “damn”, “oh my god”, “shit”, “motherfucker”, and “nigger”.